An Unusual Cause of Acute Renal Failure in a Newborn: Hydrometrocolpos - Aygün, C.; Özkaya, O.; Ayyýldýz, S.; Güngör, O.; Mutlu, B.; Küçüködük, Ş. (Springer, 2006)
Here we report on an unusual cause of acute renal failure in a newborn: hydrometrocolpos due to imperforate hymen. Hymenotomy resolved all of the laboratory and clinical abnormalities of the patient and the baby was sent home healthy. © IPNA 2006.
Keywords: Acute Renal Failure; Hydrometrocolpos; Imperforate Hymen; Newborn